An overview of diabetic foot disease - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
The incidence of diabetes globally is reaching an epidemic proportion and with it carries the risk of complications and diabetic foot disease inclusive. The pathophysiology of diabetic foot disease is multifactorial and includes neuropathy, infection, ischaemia and abnormal foot structure and biomechanics. Early recognition of the aetiology of these lesions is important for good functional outcome. Managing the diabetic foot is a complex clinical problem requiring a multidisciplinary collaboration of health care workers to achieve limb salvage. Adequate off-loading, frequent debridement, moist wound care, treatment of infection and revascularisation of ischaemic limbs are the mainstays of treatment. Even with proper management, some of the foot ulcers do not heal and are arrested in a state of chronic inflammation. These wounds can frequently benefit from various adjuvants, such as aggressive debridement, growth factors, bioactive skin equivalents and negative pressure wound therapy. We reviewed current literature including original and review articles obtained through a search of PubMed database, Medline, Google scholar and hand searching of bibliographies of published articles using the keywords: Diabetes, diabetic foot, neuropathy, peripheral arterial disease and ulceration. The enormity of the challenges associated with the management of this important complication of diabetes, coupled with the various progresses being made in this area, and the need to streamline the principles of management, especially in our environment prompted us to review this subject matter.